Frequency of the apolipoprotein E epsilon 4 allele in a case-control study of early onset Parkinson's disease. Issue 4 (October 1996) - Whitehead, A S; Bertrandy, S; Finnan, F; Butler, A; Smith, G D; Ben-Shlomo, Y
Abstract : OBJECTIVES: It has been suggested that Parkinson's disease and Alzheimer's disease may share a common or at least overlapping aetiology. The prevalence of dementia among cases of Parkinson's disease is known to be greater than expected in the general population. The frequency of the apolipoprotein epsilon 4 allele in a large case-control study of early onset Parkinson's disease has been examined. METHODS: 215 patients and 212 population based controls were recruited from the Republic of Ireland between 1992 and 1994. Cases had to have disease onset at 55 years or younger and be born after 1925. RESULTS: The frequency of the epsilon 4 allele was almost identical between cases of Parkinson's disease (14.6%) and healthy controls (13.3%). There was no relation between epsilon 4 status and disease onset, disease duration, Hoehn and Yahr score, and disease progression. The frequency of the epsilon 4 allele was not increased among 10 patients with Parkinson's disease with dementia (10.0%) compared with the other patients without dementia (14.8%). There was no association between epsilon 4 allele status and either a history of smoking, family history of dementia, or Parkinson's disease, or being born in a rural area. The odds ratio for the ApoE epsilon 4 allele associated with Parkinson's disease was 1.10 (95% confidence interval (95% CI) 0.68-1.79), adjusting for age group, sex, and residential status. The pooled odds ratio from a meta-analysis of six studies of ApoE epsilon 4 status and Parkinson's disease was 0.94 (95% CI 0.69-1.27). CONCLUSIONS: The results from our study as well as the pooled meta-analysis exclude any important role for ApoE epsilon 4 status in the development of Parkinson's disease. Our results similarly do not support its role either in dementia associated with Parkinson's disease or disease prognosis.